2021
DOI: 10.3390/plants10091808
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Characterization of ZnO Nanoparticles Using Ochradenus arabicus and Their Effect on Growth and Antioxidant Systems of Maerua oblongifolia

Abstract: Zincoxide nanoparticles (ZnO NPs) are among the most produced and used nanomaterials worldwide, and in recent times these nanoparticles have also been incorporate in plant science and agricultural research. The present study was planned to synthesize ZnO NPs biologically using Ochradenus arabicus leaves and examine their effect on the morphology and physiology properties of Maerua oblongifolia cultured in vitro. ZnO NPs were characterized by UV–visible spectroscopy (UV–vis), X-ray diffractometer (XRD), Fourier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 56 publications
2
4
0
Order By: Relevance
“…The reported absorption peaks of the ZnO NPs are in good accordance with those in previous research, where absorption peaks have been found between 355 and 380 nm. Our results agree with those of Shaikhaldein et al [ 54 ], who obtained an absorption peak at 380 nm. In a study conducted by Mahamuni et al [ 55 ], the absorption peak recorded in each spectrum was found to be in the range of 360–380 nm, which is a characteristic feature of pure ZnO.…”
Section: Resultssupporting
confidence: 93%
“…The reported absorption peaks of the ZnO NPs are in good accordance with those in previous research, where absorption peaks have been found between 355 and 380 nm. Our results agree with those of Shaikhaldein et al [ 54 ], who obtained an absorption peak at 380 nm. In a study conducted by Mahamuni et al [ 55 ], the absorption peak recorded in each spectrum was found to be in the range of 360–380 nm, which is a characteristic feature of pure ZnO.…”
Section: Resultssupporting
confidence: 93%
“…Adding zinc nitrate to the extract of O. Arubicus leads to the color change within few minutes of stirring at 60 • C (Figure 1). This is consistent with the findings of [51], who observed a change of color in the reaction mixture of plant extract and zinc acetate as an indicator to the ZnO NPs formation. When examined by UV spectrophotometry, the biosynthesized ZnO NPs showed a peak at 352 nm (Figure 2a) confirming the presence of ZnO NPs in the reaction mixture [52].…”
Section: Discussionsupporting
confidence: 93%
“…Green synthesized ZnO NPs using Ochradenus arabicus leaves were prepared as reported by Shaikhaldein et al [10]. The constituents of the preparation of ZnO NPs included zinc acetate, sodium hydroxide, and Ochradenus arabicus leaf extract.…”
Section: Zno Nps Treatmentmentioning
confidence: 99%